Corporate social responsibility and the market performance of Brazilian companies - Degenhart, Larissa; Giordani, Mikaéli da Silva; Halberstadt, Ismael Alan; Soares, Cristiano Sausen; Zonatto, Vinicius Costa da Silva (Revista de Administração da UFSM, 2020)
Purpose – This research aimed to analyze the relationship between Corporate Social Responsibility (CSR) and the market performance of Brazilian companies. Design/methodology/approach – A descriptive, documentary and quantitative research was carried out using panel data regression. The analysis period covered 2010 to 2018 and the sample comprised 41 companies. Findings – The results revealed that investments in external CSR and the fact that companies are listed on the ISE index increase their market value. The CSR information of Brazilian companies aimed at investments made for a society helps to increase market performance. Research limitations/implications – It should be noted that the results cannot be generalized for all Brazilian companies. This research contributes to the accounting and CSR literature, by analyzing the benefits of CSR on companies' market performance. Practical implications – The findings assist investors in the decision-making process, as companies that have CSR actions have positive impacts on their value, operational efficiency and the ability to generate financial performance. Social implications – The results have social implications, as they reinforce the importance of companies investing in CSR, which can improve their market value and benefit society with practices aimed at social well-being. Originality/value – CSR was analyzed in several aspects in the accounting literature. However, the focus of the relationship between CSR and specifically market performance has been little explored in Brazil, a fact that denotes research value.